In order to find the value of the composition of 2
functions, in our case f and g, we have to follow the
steps:
Step 1: First, we have to find out the expression of
the composition of the 2 functions:
(f*g)(x) =
f(g(x))
To find f(g(x)) we have to substitute x by g(x) in
the expression of f(x):
f(g(x)) = 1/(g(x) +
3)
Now, we'll substitute g(x) by it's
expression:
1/(g(x) + 3) = 1/(x +
3)
f(g(x)) = 1/(x +
3)
The next step is to calculate
(g*f)(x).
g(f(x)) =
f(x)
g(f(x)) = 1/( x + 3
)
Though the composition of 2
functions is not commutative, in this case the results of (f*g)(x) and (g*f)(x) are
equal.
No comments:
Post a Comment